NEED ASSESSMENT PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS AKTIVITAS JASMANI UNTUK KARAKTER DEMOKRATIS - Himawan, Faris; Ardiyanto, Asep; Arisyanto, Prasena (Universitas Sarjanawiyata Tamansiswa, 2021)
This research is backgrounded because there are still students who argue because they can not accept the opinion of their friends. When students are divided into groups some do not want to group with others and he only wants to group with his close friends. The study aims to look at the extent of physical activity-based learning models in grade IV elementary schools that apply games in learning to foster democratic character. The research method used is the development method or Research and Development (R&D). The subject of this study was grade IV students of Satriyan State Elementary School 02 Batang which numbered 19 students. Expert validation results show that model validation is 79%, material validation is 82%. The technique used at the time of the study was qualitative and quantitative descriptive analysis.